Methodology to analyze the structural state due to the quality of the manufacturing process using an optimized numerical approach and dynamic analysis - Menezesa, Vanessa Guimarães Soares de (2020)
The emergence of complex systems required with these systems takes charge of specific demands. This eventrequired that its constituent materials have specific characteristics. From this demand, mainly in the aeronautical environment, composite materials arose. Deviations from the expected structural properties in structures that perform high-risk functions must be strongly avoided. For this reason, preventive inspections are adopted as soon as these structures are manufactured and during their self-service. Increasingly, it demanded the improvement of these inspection systems since it was not always possible to have the necessary accessibility or visibility. The widespread adoption of Structural Health Monitoring (SHM) in aerospace structures could enhance safety and reliability. SHM includes a set of sensors that monitor structural components. Among the forms of inspection by SHM, there is the vibration method since structural changes cause changes in the natural frequency of the structure. However, the determination of this frequency range depends on the design variables of these structures that are only computationally reproduced. Computational advance in a structural analysis has been providing increasingly sophisticated evaluations. Structural optimization problems have also gained more notoriety, and these can be used to assist the quality study of the manufacturing process in composite materials. Thus, in this work, a methodology was developed to help in the non-conformities detection of the composite manufacturing process. This methodology relies on Latin Hypercube for the DoE (Design of Experiments) process, FEM (Finite Elements Method) for the numerical model of the structure, Kriging Metamodel for the development of the substitute numerical model, and EGO (Efficient Global Optimization) for the improvement of the numerical model.This research aims to evaluate a methodology to analyze the structural state due to the quality of the manufacturing process using an optimized numerical approach. The numerical model indicates the presence of manufacturing defects in composite material structures through changes in modal parameters. The main objective is achieving a numerical model that represents the natural frequencies of a composite structure reducing the computational effort.The maximum and minimum allowable frequency values are used as FRFs. These values are obtained through the points used for training the Kriging metamodel. Therefore, the research proposed a methodology to defines the natural frequency and FRFs ranges to delimit, select, and/or assesses the quality of manufactured composite components.